Professional sport players recover from coronavirus and return to competition: hopes for resuming a normal life after COVID-19 for older people - Salini, S.; Russo, A.; Biscotti, D.; Broccatelli, M.; D`elia, M.; Savera, G.; Landi, F. (Journal of Gerontology and Geriatrics, 2020)
On June 17, 2020, professional athletes started their soccer activity playing the Italian Cup final. In particular, some of them had recovered from COVID-19 one month earlier, after testing positive on different occasions, the first of which in mid March. They admitted coronavirus had taken a huge toll on their health and even left struggling to breathe. Few days later many other professional soccer athletes of other Italian teams re-started playing League A. Similarly, other professional athletes who have suffered from COVID-19 slowly recovered and resumed their sports at a competitive level declaring to have struggled for a long time during recovering period. The stories of many professional athletes around the world have attracted particular attention from the media. However, most COVID-19 survivors On June 2020, many professional soccer athletes of Italian teams re-started playing League A. Some of them recovered from COVID-19, resumed their sports at a competitive level declaring to have struggled for a long time during recovering period. Most COVID-19 survivors (especially older people) are not professional athletes; these persons cannot generally benefit from a dedicated staff during recovery. This is why it is really important to provide rehabilitation and physical exercise protocols for adults and/or older people who have recovered from COVID-19. To this aim, the post-COVID-19 service of Fondazione Policlinico Universitario A. Gemelli (Rome, Italy) has developed specific physical activity programmes. The physical activity protocol of "SPRINTT", a European project aimed at preventing mobility disability in frail older people with sarcopenia, has been re-shaped to adapt it to COVID-19 survivors. This personalized program includes aerobic, strength, flexibility, and balance training. Accumulating evidence supports regular physical activity, in combination with appropriate nutritional support, as the most effective strategy for improving sarcopenia and physical function. More studies are needed to determine if this may be more valid in COVID-19 patients.